PENGEMBANGAN MEDIA E-LEARNING BERBASIS MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) - I Putu Dedy Wirawan (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
In teaching learning process, the form of teaching learning cooperative typed STAD (Student Team Achievement Division) is able to be done when it is applicated in the school. Media e-learning can be used the teaching learning type STAD and can be done everywhere. E-learning is the conventional of cooperative that is used in digital format though the internet technology. With casting the concept of teaching learning of STAD to the e-learning, it will make e-learning to be more innovative.  This research will be developed in one of media e-learning based on the type of teaching learning cooperative of STAD (Student Team Achievement Division). This research is the fundamental research, so in the implementing use the method of standard in improving that use the method System Development Life Cycle (SDLC) with model Waterfall. The improve or expand the software in Waterfall model begins from the level system and move to expansion of the advance steps from analysis phase, desain, coding, operation and maintenance.   The output of research is the media e-learning in teaching learning model of cooperative type of STAD (Student Team Achievement Divison) that has been designed in using DFD (Data Flow Diagram) with the three entities that are administrator, teachers and students. The media has been expanded or built to use the language program of PHP and MySQL as the base of data. This media has been equitable with the step of teaching learning cooperative type STAD so it has been one of media alternative that can simflity the teachers in teaching model of teaching learning cooperative type STAD (Student Team Achievement Divison).